EDUKASI PEMBUATAN SABUN CAIR CUCI PIRING PADA PASIEN SKIZOFRENIA DI RSJ SURAKARTA - Fuadi, Ahmad M; Lestari, Ayu; Ath-Tariq, Muhammad Arhab; Fitri, Zada Almira (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2024)
The types and characteristics of mental disorders are very diverse, one of which is oftentreated is schizophrenia. At the Surakarta Regional Mental Hospital (RSJD) thenumber of schizophrenia patients is relatively large. It is estimated that more than 90%of schizophrenia patients experience hallucinations. To minimize the impact ofhallucinations, appropriate treatment is needed. Group activity therapy is a therapeuticmodality which is an effort to facilitate nurses or psychotherapists with a number ofpatients at the same time. The aim of this service activity is to provide provisions topatients and provide therapeutic activities to increase the level of hallucinations inpatients. The educational activity of making liquid dishwashing soap is an alternativeto fulfill this activity. The activity was carried out at RSJD Surakarta.